Effect of Play Group and Biopsychosocial Factors on the Independence Development of Preschool Children in Surakarta - Marlinawati, Iin Tri; Salimo, Harsono; Murti, Bhisma (Journal of Maternal and Child Health, 2017)
Background: The development of children’s independence is important for their future competitiveness in the rapidly increasing social changes. Disturbance in the development of children